CO2 emissions, economic growth, renewable and non-renewable energy production and foreign trade in China - Chen, Yulong; Wang, Zheng; Zhong, Zhangqi (Renewable energy, 2019)
Based on the autoregressive distributed lag (ARDL) bounds testing approach and vector error correction model (VECM) Granger causality approach, this paper explores the relationships among per capita carbon dioxide (CO2) emissions, gross domestic product (GDP), renewable, non-renewable energy production and foreign trade for China covering the period 1980–2014. One finding is that there is a long-run relationship among those variables. Another important finding is that China does not have the Environmental Kuznets Curve (EKC) of CO2 emissions under the influence of economic growth, non-renewable energy production and foreign trade. However, after the addition of renewable energy production variable, it is found that the inverted U-shaped EKC hypothesis is supported in the long-run. Our long-run estimates show that increasing non-renewable energy and GDP increases CO2 emission, whereas renewable energy and foreign trade have a negatively impact on CO2 emissions. The short-run Granger causality tests show that there are bidirectional causalities running from foreign trade, CO2 emission and non-renewable energy to renewable energy. Furthermore, the finding indicates that renewable energy consumption is a key solution in reducing CO2 emissions over time. Finally on the basis of this study, we put forward the corresponding countermeasures and suggestions on China's carbon emission reduction strategy. •Examine the relationships among CO2 emissions, renewable energy and trade.•It is found that the inverted U-shaped EKC hypothesis is supported.•Renewable energy and trade have a negative impact on CO2 emissions in the long-run.•There is bidirectional causality running from CO2 emission to renewable energy.